Health Promoting Behaviours among Adolescents of Government School in Kalika Municipality, Chitwan - Amrita Paudel; Sujata Neupane; Sumnima Shrestha; Mamta Chhetri; Subash Koirala (Med Phoenix, 2026)
Introduction: Health-promoting behaviours (HPB) established during adolescence promote lifelong health and prevent chronic diseases. This study assessed HPB among school-aged adolescents. Materials and Methods: A cross-sectional study was conducted from February to April 2021 among adolescents aged 10–19 years studying in grades 9 and 10 at a government school in Kalika Municipality, Chitwan, Nepal. Data were collected using a semi-structured questionnaire and the Adolescent Lifestyle Profile–Revised 2 (ALP-R2). Descriptive and inferential analyses were performed using SPSS version 20. Results: Among 322 respondents, 51.6% demonstrated a satisfactory level of HPB. Significant associations were found between HPB and sex and fathers’ occupation. The highest mean scores were observed in positive life perspective and health responsibility, whereas physical activity had the lowest score. Conclusion: More than half of the adolescents exhibited satisfactory HPB. However, low physical activity highlights the need for targeted interventions. Sex and fathers’ occupational status were significant determinants of HPB.